(untitled) (Archives of Criminology, 1991)
What this essay does, is re-tell the history of revisionist thinking about crime and its control over the last 20 years. Anti-criminology was a highly self conscious enterprise. Very soon after its initial apearance, it was marked by self-doubt and eventually a series of major internal revisions. The initial changes in anti-criminology appeared as it began to absorb the implications of its own creations. This was followed by a further set of mutations forced by having to reconsider its relationship to an external (mainly political) world. By the middle and more clearly, the end of the Seventies, liberals and radicals began to publish evaluations of what had happened to the original vision. The conclusion was dismal. The visualized reforms had not been put into practice at all or they had been put into practice for the wrong reasons or they had been co-opted and absorbed in such a way as to completly blunt their radical edge. The old structures had not only turned out more resilient than we thought but the “alternatives” now overlaid on the existing system had actually made matters worse: coersive social control is disguised, the net of state control widenes. Four relevant political responses began to emerge. First, “radical impossibilism" – a re-statement of the traditional belief that no progressive reforms are possible without a major restructuring of the whole political economic order; second, “liberal realism” – a sense of caution, scepticism and even despair, a further lowering of the (already diminished) liberal horizon; third, “re-affirmation” – an attempt to show (as the European abolitionists are doing) just what a literal translation of the original vision would have to look like; fouth, “left realism” – a retention of socialist principles, but this time with a willingness to engage in socia reform, a determination to be “relevant’” and a denunciation of the original vision as romantic and utopian. The main features of currently dominant “left realist” position are: 1) Instead of demystifying the crime problem as a product of media myths, moral panic or false consciousness, crime is now acknowledged to be a real problem. There is a rational core to the fear of crime. One cannot gloss over the demoralization and disorganization which are both the causes and products of predatory and violent crime. 2) Although the particular psychological form it took was misconceived, the original positivist enterprise of finding the causes of crime was fully justified. Just when mainstream crimonology has abandoned these aetiological questions in favour of a know-nothing managerialism, so must radicals return to the obvious contexts in which crime emerges in modern society: poverty, racism, deprivation, social disorganization, unemployment, the loss of community. 3) Older idealist notions ‒ such as the elevation of the criminal into a “primitive robel” or crypto-political actor – must now be finally repudiated. And historical analysis, while important for building a sociology of law, is no real substitute for solving the traditional problems of criminology. 4) Radical criminology, then, must make itself politically relevant by operating on the very same terrain which conservatves and technocrats have appropriated as their own. It cannot afford to risk the errors of the Sixties by allowing itself to be marginalized. In short, left rearism is realistic. This, it is argued, is where any credible alternative to mainstream criminology must be constructed. The heady mixture of well meaning liberalism, romantic anarchism and a new left style marxism which characterized the initial phase of anti-criminology could hardly together for very long. As I have just recorded, these ingredients were soon separated out. A theoretically purer Marxism, a visionary anarchism, re-constituted liberalism and finally, left realism, all emerged as destinctive political stances against mainstream criminology. Any attempt to explain the fate of anti-criminology must avoid a narcisstistic exaggeration of its importance. These ideas were diffused with commitment and enthusiasm and they reached the centre of the criminological enerprise. But at no point has the theoretical or political momentum been strong enough to pose a real threat to a dominant tradition. Finally let me set out the wider spectrum of styles available in academic criminology today. The single criterion of this typology is ideology. 1) Conservative: the traditional conservative model stresses the primacy of law and order, a strengthening of the legal and penal system, classical doctrines of punishment such as deterrence, a moral crusade against permissiveness and lack of authority as the sources of crime. The reconstituted, neo-conservative version retains the values of the original but is more pragmatic, more selective about the use of state power, less ambitious or fundamentalist in its commitment to restoring a lost social hierarchy. 2) Managerial: this style overloeps closely with neo-conservatism but it professes to be wholly non-ideological, pragmatic and technocratic. Energy is devoted to only one of three criminological questions: that is, how to design an effective crime control policy. 3) Liberal: there are three variants of liberalism now. The most traditional version retains the programme of pre-Sixties positivism – treatment, rehabilitation, reform, individualization. The second variant is the neo-liberalism. It supports the due process rather than crime control model. A third variety of liberalism is now emerging. Its theory of crime causation is virtually identical to that of left realism, but its overall political programme and geneology is close to “genuinely” liberal of social democratic goals. 4) Socialist: the traditional version locates crime in the total system of inequality and dominance in capitalist society, rejects mere reformism and looks towards a revolutionary change in the social order which will result in socialist legality. The reconstituted version is left realism. 5) Abolitionist: it remains faithful to most of the components in the initial anti-criminology vision. In particular, it takes as a literal truth the original set of insights about the relativity of the criminal/penal law model as a form of categorisation and social control. 6) Theoretical: it is content to leave to others any political implications of its work. The commitment is to sociology and to the integrity of knowledge as a value in itself, not a subordinate to any other interests.